The effect of work-family conflict and flexible work arrangement on turnover intention: do female and male employees differ? - Nastyalita Gunaprasida; Amin Wibowo (Jurnal Siasat Bisnis, 2019)
The purpose of this paper is to examine the effect of work-family conflict, and flexible work arrangements as moderating variable on the intention to leave for female and male employees.  The population in this study is hotel employees in Yogyakarta. The sample population chosen was hotel employee who has married, has children, and does not live with parents and parent in-law. Overall, work-family conflict positively influenced intention to leave. There is difference result in regard to moderating variable, as for the female employees a flexible work arrangement moderates the relationship between work-family conflict and turnover intention, while for male workers the moderating effect is not significant. The practical implication is turnover intention can be avoided by creating and developing comfortable work condition and environment where supervisor and colleagues are supporting each other. By developing a comfortable atmosphere, it is expected that negative emotions triggering work-family conflict will be eliminated so employees do not have any reason to leave the organization anymore, especially to women employees. This study offers a new insight which gender might take important roles in the utilization of flexible work arrangements. It is suggested for future research that considering sample population from other industries such as banking industry and hospital may make research more generalizable.